Euxoa capsensis Chrétien, 1911 a new Noctuidae species for Europe and the Maltese Islands, including an updated Noctuoidea checklist for the Maltese Islands (Lepidoptera: Noctuidae, Noctuinae) - Jonathan Agius (SHILAP, 2024)
Euxoa capsensis Chrétien, 1911 is reported for the first time from Europe and the Maltese Islands. Notes on the distribution and habitat of the adult are included. A Maltese name is proposed for this new record.